Effect of solar UV/EUV heating on the intensity and spatial distribution of Jupiter's synchrotron radiation. Issue 10 (3rd October 2013) - Kita, H.; Misawa, H.; Tsuchiya, F.; Tao, C.; Morioka, A.
<x xml:space="preserve">Abstract</x> [1] We analyzed the Very Large Array archived data observed in 2000 to determine whether solar ultraviolet (UV)/extreme ultraviolet (EUV) heating of the Jovian thermosphere causes variations in the total flux density and dawn‐dusk asymmetry (the characteristic differences between the peak emissions at dawn and dusk) of Jupiter's synchrotron radiation (JSR). The total flux density varied by 10% over 6 days of observations and accorded with theoretical expectations. The average dawn‐dusk peak emission ratio indicated that the dawn side emissions were brighter than those on the dusk side and this was expected to have been caused by diurnal wind induced by the solar UV/EUV. The daily variations in the dawn‐dusk ratio did not correspond to the solar UV/EUV, and this finding did not support the theoretical expectation that the dawn‐dusk ratio and diurnal wind velocity varies in correspondence with the solar UV/EUV. We tried to determine whether the average dawn‐dusk ratio could be explained by a reasonable diurnal wind velocity. We constructed an equatorial brightness distribution model of JSR using the revised Divine‐Garrett particle distribution model and used it to derive a relation between the dawn‐dusk ratio and diurnal wind velocity. The estimated diurnal wind velocity reasonably corresponded to a numerical simulation of the Jovian thermosphere. We also found that realistic changes in the diurnal wind velocity could not cause the daily variations in the dawn‐dusk ratio. Hence, we propose that the solar UV/EUV related variations were below the detection limit and some other processes dominated the daily variations in the dawn‐dusk ratio.